A comparative study of the Turkish and German health care systems with regard to quality management in psychiatric hospitals - Fatma Kantas Yilmaz; Tarik Naci Norbert Ugur; Michael Rese (International Journal of Management, Economics and Social Sciences (IJMESS), 2019)
This paper investigated the delivery of health services based on data recorded at two medium-sized hospitals: Erenkoy Mental Health Research and Training Hospital located in Istanbul/Turkey and LVR-Klinik Viersen in Germany. A comparison of quality management systems in terms of certification and accreditation procedures, satisfaction of patients and health care professionals as well as quality indicators revealed structural similarities and differences in health care practices. Both quality management systems have been undergoing radical changes. Social health insurance system was established in Germany in 1880s and the primary intention was to incorporate the entire society in the scope of health care services. In the framework of the Health Transformation Project in Turkey, tremendous changes have been made since 2003 and a General Health Insurance System, which is similar to the health care system in Germany, was set up. Differences are observed in the delivery of health care services in both countries, in which health care expenditures have increased in recent years. In this paper, health care systems in Germany and Turkey are examined based on on-site examinations, which were conducted in December 2016 - February 2017 in LVR-Klinik Viersen, Germany. Quality studies performed in the hospitals in Germany and Turkey were comparatively discussed. Similar to a high number of other countries, quality practice gained importance along with reform studies that were performed in health care systems in Germany and Turkey. Several studies on the hospital quality of both countries pointed out to some practical differences, although similarities were also found.
Keywords: I10; I11; I12; I18; I19; 330; Health care system; Germany; Turkey; hospital quality management; health insurance system